2020
DOI: 10.1002/adts.202000138
|View full text |Cite
|
Sign up to set email alerts
|

Critical Layer Thickness Analysis of Vertically Stacked Hyperbolic Metamaterials for Effective Negative Refraction Generation

Abstract: Vertically stacked narrow metal‐dielectric multilayered structures known as vertical hyperbolic metamaterials (vertical HMMs) are proposed for broadband negative refraction. The thickness of each layer is required to be subwavelength for effective medium theory (EMT) to be applicable. Therefore, each layer should be thin, forcing the aspect ratio to become extremely high. This requirement makes the fabrication of vertical HMMs difficult. Thus, it is important to determine the limit of the layer thickness for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…5b). A numerical study of the critical layer thickness of vHMMs in the visible region has been reported [125]. A variety of vHMMs composed of various materials have been numerically investigated to determine the critical layer thickness of the potential for negative refraction utilization.…”
Section: Light Propagation and Manipulation Using Hmmsmentioning
confidence: 99%
“…5b). A numerical study of the critical layer thickness of vHMMs in the visible region has been reported [125]. A variety of vHMMs composed of various materials have been numerically investigated to determine the critical layer thickness of the potential for negative refraction utilization.…”
Section: Light Propagation and Manipulation Using Hmmsmentioning
confidence: 99%
“…For example, chiral metamaterials, consisting of meta‐atoms lacking any mirror symmetry planes, can selectively absorb left or right circularly polarized light (LCP and RCP, respectively) 18–26 . Also, hyperbolic metamaterials, which are composite materials made up of dielectric and metallic subwavelength‐layers, are able to possess high wavevector modes inside 27–33 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, except for a positive uniaxial crystal, 13 a uniaxially anisotropic material with a hyperbolic dispersion relationcommonly known as a hyperbolic metamaterial (HMM) has become a fascinating candidate for achieving optical negative refraction. [14][15][16] Especially, a planar metal/dielectric single-periodic multilayer at lens operating at ultraviolet (UV) wavelength was proposed, 17 which demonstrates a clear focus in air 350 nm away from the surface of the at lens through simulation and experiment. However, to the best of our knowledge, there are no reports about studies of planar UV objectives based on optical negative refraction for nanolithography applications.…”
Section: Introductionmentioning
confidence: 99%